Analisis Penerapan Sistem Pembayaran Termin pada Kerja Sama Pemanfaatan Lahan PT Pelabuhan Indonesia (Persero) Regional 4 Bitung - Nurmala Sari Masloman; Ivonne Helena Putong; Treesje Lusje Runtuwene (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study aims to analyze the implementation of the installment payment system in land use cooperation at PT Pelabuhan Indonesia (Persero) Regional 4 Bitung, analyze revenue recognition based on PSAK 72, and identify the advantages and disadvantages of implementing the installment payment system in the land use cooperation. Using a qualitative descriptive method with data collection techniques through interviews and documentation. The results of the study indicate that the installment payment system in land use cooperation is implemented through six payment stages according to the cooperation agreement. Revenue recognition for the cooperation is carried out based on the company's rights arising from the contract and is not dependent on cash receipts. Payments that have not been received are recorded as accounts receivable in accordance with accrual-based accounting principles and the provisions of PSAK 72 concerning Revenue from contracts with Customers. The implementation of the installment system provides advantages such as increasing payment convenience for partners, supporting opportunities for cooperation, and assisting the company in cash flow planning. In addition, installment payments also have disadvantages in the form of increasing accounts receivable which have the risk of bad debts and late payments so that more supervision is needed. Based on the research results, the conclusion of the implementation of the installment payment system in the land utilization cooperation of PT Pelabuhan Indonesia (Persero) Regional 4 Bitung has been implemented in accordance with the cooperation agreement and the recognition of revenue is in accordance with PSAK 72.